UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) PADA PENGGUNAAN APLIKASI AKUNTANSI TERHADAP KINERJA KARYAWAN - Hartini, Sari; Afnisari, Karnita (Jurnal Pilar Nusa Mandiri, 2013)
Rapid technological growth now gives a huge influence, not least in the field of business, coupled with the globalization that requires a company to have a quick way of working to provide services to its customers, and also the updated reports at any time, it is needed by the company to be able to survive and be competitive with other companies. Data loss caused due to an error in the push of a button or the result of a computer virus that is very disturbing that many Perusahaan. Data activity can cause the data search process requires considerable time. In theory, processing and accounting data processing became more effective with the help of a computer, but not necessarily the data manually processing becomes ineffective, so it is very important to evaluate the effectiveness of the accounting system can be assessed from the aspects of data security, time, accuracy, relevance, variety of reports, and comfort physical. During the computer-based accounting system implemented in the Cooperative PT. NISSINMAS does not know the effectiveness of computer-based accounting information system is implemented. Though the importance of knowing the effectiveness of computer-based accounting information system applied by the company, because by knowing the level of effectiveness, the company can measure the success of computer-based accounting information system has been implemented in line with expectations. This is the background to research based on the assessment of the effectiveness of computer-based accounting information systems in cooperative PT. NISSINMAS. This study will examine the effectiveness of the use of information systems user accounting application for enterprises based on the factors that influence the approach of a unified theory of acceptance and use of technology (UTAUT). Statistical tests performed using Structural Equation Modeling (SEM) using AMOS software.